Successes and Challenges of The EU External Aviation Policy. (c2018) - Mazloum, Hamza Sobhi (2018)
An industry that is more than a hundred years old, commercial aviation first started in 1914 when the first scheduled revenue flight was operated. Commercial aviation currently carries more than four billion passengers annually and more than one third of the value of international trade. The economic and political environment of international air transport cannot be understood without comprehending the legal hurdles that are fraught with the concept of “airspace sovereignty”. The establishment of a “protectionist air transport regime” in the twentieth century (following the two World Wars) was primarily intended for security and prestige reasons. The focus of this study is to identify the regulatory landscape and the core of the international air transport regime before highlighting the European experience in integrating its skies as a single market and developing its external aviation policy under a “single voice” mandated to the European Commission. This study will underscore the positive impact of European integration in the realm of air transport, which also led to the inception of the EU external aviation policy in the global system. It further argues that this EU policy faces a myriad of internal and external regulatory complexities that constrain the Commission’s negotiations power and its tailored-approach towards its targeted non-EU states to reach Comprehensive or Open Skies Agreements, due to internal prerequisites mandated by EU member states to the Commission and external socio-economic and political challenges from potential signatory third states. Moreover, the EU external aviation policy is bounded by the weakening of its air transport competitiveness against foreign actors and is obstructed by the challenge of successfully implementing such agreements in full. This study will zoom in on four cases that highlight the aviation relations between the EU and each of Morocco, Lebanon, the USA and the UAE. These cases will highlight the challenges the EU is facing and the repercussions on the global system.